2019
DOI: 10.1016/j.lwt.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and identification of adulteration in the fat content of chicken hamburgers using digital images and chemometric tools

Abstract: Argentina is a beekeeping country and one of the drawbacks is the exposure of the hives to pollutants. Therefore, the aim of this Thesis is the development of an electroanalytical methods to evaluate the hygienic-sanitary quality of bee products of Buenos Aires province. The following works were performed: ➢ A "lab-made" solid bismuth electrode was designed for cadmium determination in corbicular pollen and raw propolis samples. For this proposed, Square Wave Anodic Stripping Voltammetry was used as electroana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Moreover, a 91.9% accuracy rate was achieved for the classification of the aged cachaças into nonadulterated and adulterated samples and a 100% classification accuracy to identify wood types alone using blue histogram. Fernandes et al 15 identified adulterations in chicken hamburgers with a fat content higher than 20% (w/w), as limited by Argentinean legislation. SPA-LDA coupled with grayscale + HSI histogram attained the most satisfactory result with correct classifications of 92.0% and 95.8%, sensitivities of 94.1% and 90.0% and specificities of 90.9% and 100% for both training and test sets, respectively.…”
Section: Identification Of Food Adulterationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a 91.9% accuracy rate was achieved for the classification of the aged cachaças into nonadulterated and adulterated samples and a 100% classification accuracy to identify wood types alone using blue histogram. Fernandes et al 15 identified adulterations in chicken hamburgers with a fat content higher than 20% (w/w), as limited by Argentinean legislation. SPA-LDA coupled with grayscale + HSI histogram attained the most satisfactory result with correct classifications of 92.0% and 95.8%, sensitivities of 94.1% and 90.0% and specificities of 90.9% and 100% for both training and test sets, respectively.…”
Section: Identification Of Food Adulterationsmentioning
confidence: 99%
“…Similar to what happens in applications involving classification, the main publications that use multivariate calibration in CACHAS has been directed mostly to food analysis. 15,30,31,[43][44][45]55,56,58 In addition, applications in agricultural, 46,49 microbiological 53 biological, 54 drug, 18 biofuel, 57 and mineral insulating oil 59 analyses have also been carried out. Here, although most of the studies do not also employ sample pretreatment, solvents, or reagents, the calibration models are dependent on the values obtained by reference methods or similar accurate measurements of the target property/analyte.…”
Section: Multivariate Calibrationmentioning
confidence: 99%
See 3 more Smart Citations